130k views
3 votes
Solve by substitution:2x-3y=-1y=x-1

User Raychi
by
6.0k points

1 Answer

3 votes

Given:


\begin{gathered} 2x-3y=-1 \\ y=x-1 \end{gathered}

Sol:.


y=x-1

Substitution yhe value of "y" in first equation:


\begin{gathered} 2x-3y=-1 \\ y=x-1 \\ 2x-3(x-1)=-1 \\ 2x-3x+3=-1 \\ -x+3=-1 \\ 3+1=x \\ x=4 \end{gathered}

So the value of "y" is:


\begin{gathered} y=x-1 \\ y=4-1 \\ y=3 \end{gathered}

So the value of x is 4 and y is 3.

User TwistedOwl
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.